Enhancing Operational and Service Performance in Revitalized Markets: A Case Study of Pasar Pon Kabupaten Trenggalek - Palupi, Endah; Usman, Fadly; Prayitno, Gunawan; Biloshkurskyi, Mykola V.; Neshchadym, Liudmyla M. (Journal of Regional and Rural Studies, 2025)
The revitalization of Pasar Pon Kabupaten Trenggalek aimed to enhance its role as an economic hub, but post-revitalization challenges have limited its effectiveness. A formal structure for market management has not yet been put in place, and its key roles and responsibilities, especially those related to managing the market and maintaining the building after the revitalization, remain undefined. This study evaluates and provides recommendations for improving the operational and service performance of Pasar Pon using SNI 8152:2021 standards, Importance-Performance Analysis (IPA), and Quality Function Deployment (QFD). Operational performance achieved a 63.6% compliance rate, revealing deficiencies in cleanliness, zoning, and management structures. Service performance, based on user feedback, highlighted critical areas requiring attention, including the number and quality of retail services and ATMs. Data collection included observations, questionnaires, and interviews, with analysis focusing on compliance with regulatory standards, user satisfaction, and prioritization of improvements. The QFD results identified clear management structures, streamlined vendor regulations, and digitalization as top priorities for enhancing performance. Findings suggest that addressing these gaps could significantly improve trader engagement, increase visitor satisfaction, and reinforce the market's economic role. This study contributes to the discourse on market revitalization by showcasing the integration of traditional market functions with modern standards and digital tools. The recommendations offer a roadmap for policymakers and market managers to implement sustainable improvements.